PROTOTYPE PEMBELAJARAN PLURILINGUAL DAN PLURIKULTURAL BERBASIS BUDAYA JAWA PADA PEMBELAJARAN BIPA - Prima Vidya Asteria; Aisyah Nur Afni (Universitas Negeri Surabaya, 2023)
This research discusses the understanding of cultural aspects that have an important role in implementing learning, especially for BIPA students. this is studied because BIPA is essentially a learner of Indonesian culture to foreign speakers who learn Indonesian. This study also uses the type of R&D research which consists of five stages in its analysis, namely analyze, design, development, implementation, and evaluation. The objectives obtained from this research are regarding the development process and the quality of teaching materials made for plurilingual and pluricultural learning based on Javanese culture, for BIPA learners. the development of this teaching material intends to facilitate BIPA learning to learn Indonesian, adapt to the plurilingual and cultural differences that exist in every society, especially in Javanese culture. The conclusions obtained from this study are that teaching materials for plurilingual and pluricultural learning based on Javanese culture for BIPA students with the theme of historical heritage temple sites in East Java are feasible to apply in learning.